Role of Artificial Intelligence (AI) Adoption and Digital Transformation in Enhancing Sustainable Business Performance: The Mediating Effect of Green Product Innovation - Gohar Mahmood; Allah Ditta; Muhammad Ramzan; Zahid Abbas (Journal of Accounting and Finance in Emerging Economies)
Purpose: adoption and digital transformation on sustainable firm performance, with a specific focus on the mediating role of green innovation practices. It aims to uncover how advanced digital technologies and AI can drive sustainability through innovation in manufacturing firms.